2023
DOI: 10.18267/j.aip.187
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Security and Interoperability of Electronic Health Record Sharing Using Blockchain Technology

Abstract: Blockchain is regarded as a significant innovation and shows a set of promising features that can certainly address existing issues in real time applications. Decentralization, greater transparency, improved traceability and secure architecture can revolutionize healthcare systems. With the help of advancement in computer technologies, most healthcare institutions try to store patient data digitally rather than on paper. Electronic health records are regarded as some of the most important assets in healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, the security challenges associated with patient data storage in IT systems have hindered the progress of ehealthcare. The introduction of blockchain technology offers a potential solution, which is explored in the work outlined in reference [16]. This research establishes the foundation for blockchain-based health information management, encompassing a public ledger, private ledger, smart contracts, and context-based access control.…”
Section: Literature Review: Related Studiesmentioning
confidence: 95%
“…However, the security challenges associated with patient data storage in IT systems have hindered the progress of ehealthcare. The introduction of blockchain technology offers a potential solution, which is explored in the work outlined in reference [16]. This research establishes the foundation for blockchain-based health information management, encompassing a public ledger, private ledger, smart contracts, and context-based access control.…”
Section: Literature Review: Related Studiesmentioning
confidence: 95%
“…The potential advantages of utilizing blockchain technology in healthcare have been the subject of several research [20], [26], [31], [32]. For instance, a thorough analysis of the literature by Puneeth et al [26] revealed the potential benefits of blockchain technology in the healthcare industry, including enhanced data privacy, security, and interoperability, as well as higher efficacy and transparency. Similarly, a study by Baysal et al [33] examined the potential application of blockchain technology to address problems with data ownership, access, and permission in the healthcare sector.…”
Section: Blockchain Technology In Healthcarementioning
confidence: 99%
“…Cloud-based EHR systems provide the benefits of accessibility, scalability, and cost-effectiveness, but they also raise concerns about data security and privacy [26]. With the use of cloud-based EHRs, healthcare practitioners can access patient data at any time and from any place because they are hosted on remote servers and made accessible online.…”
Section: Cloud-based Ehr Systemsmentioning
confidence: 99%
See 2 more Smart Citations